Identifikasi Kebutuhan Pembelajaran pada Pendidikan Dasar Kelas Rendah MI Plus Asy- Syukriyyah Tangerang - Odicus, Dimas Andre; Oktaviani, Dina (ALSYS, 2022)
The learning needs of each student at the MI PLUS ASY-SYUKRIYYAH TANGERANG school need to be identified as the basis for preparing learning and learning programs. Because the learning needs that have been identified will provide direction where the program is aimed and run in the future. identification of educational needs starts from identifying the conditions that occur in the process of implementing learning with the expected conditions in learning, followed by the process of implementing problem solving that occurs in learning and evaluating the effectiveness and efficiency of learning.